The Pitch Walk, Port of Spain, Trinidad - Rice, Ben (My University, 2009)
The Pitch Walk that encircles the entire Queen's Park Savannah passes through the tall trees that also surround the park.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Trees--Trinidad and Tobago; Roads--Guard fences; Sidewalks--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1910]; Mountains--Trinidad and Tobago; Parks--Trinidad and Tobago; Fences--Trinidad and Tobago; Pavements--Trinidad and Tobago; Pedestrian areas--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)